Kajian Apologetis Terhadap Kontroversi Kemanusiaan Dan Ketidakbersalahaan Yesus Kristus - Heryson Butar-Butar (Manna Rafflesia, 2021)
The context of understanding the humanity and innocence of Jesus gave rise a theological controversy. The reason is, the all-perfect God who became human in Jesus Christ is difficult to maintain because He is a limited figure and is considered to have made mistakes. For example Jesus' ignorance regarding the person who touched His robe (Mark 5:30-32 and Luke 8 :45), Jesus' ignorance of what will happen in the last days (Mark 13:27-32), Jesus' mistake in calling Zechariah son of Berechiah (Matthew 23:35; 2 Chronicles 24:20) and the wrong behavior of Jesus who was angry in the Temple (Matthew 21:12-16; Luke 19:45-46; John 2:15-16). The purpose of this study is to provide a biblical description in an apologetic frame as a form of a refutation of these assumptions. This study uses a qualitative method with an apologetic approach. An understanding of the person of Jesus needs to be seen comprehensively with the context that binds it. The assumptions about Jesus' guilt and ignorance are not substantially based on a comprehensive and credible interpretation.